Para além do cinema: o cineclubismo de Belo Horizonte (1947-1964) - Geovano Moreira Chaves (2010)
The cineclubism. from Minas Gerais emerged in the middle of the twentieth century, mainly in Belo Horizonte city. It corresponds to areas of important existing links between aesthetics and politics via the movies, mostly by having performed a important role regarding the production and diffusion of cinematographic theories, critiques, languages and schools until then consolidated. Such situation has made that cineclubism. one of the most important critique and theory diffuser poles, and also for the international cinematography in Brazil. The CEC (Centro de Estudos Cinematográficos) and CCBH (Clube de Cinema de Belo Horizonte) cinema clubs were the most highlighted ones due to the existence of a coherent set of political and aesthetical elements that, by relating themselves, have allowed the individuals and collectivities that frequented those places via Catholicism in its most conservative side, or via defeating communist or even existentialist ideologies to define their identities. We have taken into consideration the propagation of the cinematographic productions and vanguards, surveying the political ideologies positioning associated to aesthetic languages, such as some moments of reception and interpretation of movies inside the cinema clubs by the specialized critique, in order to historically comprehend and reveal the meaning those cineclubists. intended to assign to the movies.In last century.s Belo Horizonte, the cinema club movement has also performed a important role regarding the political and aesthetical reflection about the national repercussion events of that moment. Such propagation was mostly demonstrated in the magazines produced by those cinema clubs that associated cinema to several themes.Determining the meaning the cinema should have towards the audience and the specialized critique was also the aim of those cineclubists., that allied cinematographic aesthetics to moral and political positions. They wanted to assign meanings and identities to the regulars of those places, including by cinematographic schooling, each one by their means, taking in consideration their common views and conceptions of past, present and future, as a way of sustaining their argumentations and projects according to their respective engagements.